Hierarchical Porous Integrated Co1−xS/CoFe2O4@rGO Nanoflowers Fabricated via Temperature‐Controlled In Situ Calcining Sulfurization of Multivariate CoFe‐MOF‐74@rGO for High‐Performance Supercapacitor. (6th September 2020) - Ren, Chongting; Jia, Xu; Zhang, Wen; Hou, Ding; Xia, Zhengqiang; Huang, Dashuai; Hu, Jun; Chen, Sanping; Gao, Shengli
Abstract: The precise synthesis of electrode materials that integrate highly redox‐active transition‐metal oxide with conductive transition‐metal sulfide has always been a challenge, due to the extraordinarily robust coordination affinity of sulfur for transition metals. Herein, through controlling the calcined sulfurization temperature to stimulate the activity of oxygen to compete with sulfur, an integrated Co1− x S/CoFe2 O4 @rGO nanoflower is fabricated in the range of 780–830 ° C by employing well‐designed Co0.8 Fe0.2 ‐MOF‐74@rGO as precursor. The hierarchical‐pore structure evolved from the bimetallic MOF@rGO provides a suitable electrolyte environment to promote fast Faradaic reactions, which endows Co1− x S/CoFe2 O4 @rGO with a high specific capacity of 2202 F g −1 and remarkable cycling stability (90% after 20 000 cycles), superior to those of the most well‐known metal‐organic framework (MOF) derived systems. The assembled Co1− x S/CoFe2 O4 @rGO//AC asymmetric supercapacitor shows an outstanding energy density up to 61.5 Wh kg −1 at a power density of 700 W kg −1 . A combined experimental and density functional theory calculation demonstrates that the merged Co1− x S/CoFe2 O4 interface with optimized electronic structure facilitates electron transfer pathways and realizes the effective synergy of high redox activity from CoFe2 O4 and good conductivity from Co1− x S, leading to the excellent electrochemical performance of the material. Additionally, the formation mechanisms of the temperature‐controlled different phases are systematically investigated. Abstract : An integrated Co1− x S/CoFe2 O4 @rGO nanoflower is prepared by finely‐adjusting the in situ calcined sulfurization temperature. As a positive supercapacitor electrode material, the hybrids with the hierarchical‐pore structure provide unobstructed channels for electron shunting and electrolyte ion diffusion, showing an excellent specific capacity of 2202 F g −1 and remarkable cycling stability (90% after 20 000 cycles).